CP-082 Difference in effectiveness and safety of triple therapy-based treatment between Mono and Co-infected hepatitis C patients. (24th March 2015) - Carmona, P; Gayán, MJ; Lopez, G; Lizardi, A; Iribarren, J; Von Wichmann, M; Ercilla, M; Ripa, C; Lombera, L; Bachiller, MP
Abstract : Background: Triple therapy-based treatment with protease inhibitors in infected genotype 1 hepatitis C (HCV) patients improves efficacy measured as sustained virological response (SVR). Purpose: To compare the effectiveness and safety of triple therapy-based treatment in mono-infected and co-infected HCV-HIV patients. Material and methods: All treatments started between 2012/07/01 and 2013/12/31 were analysed. A retrospective evaluation was made of electronic medical records and outpatient pharmacy records. SVR was defined as undetectable viral load at week 60. Results: 83 patients were included, 80 treated with telaprevir and 3 with boceprevir, 58 mono-infected and 25 co-infected patients. Baseline characteristics in mono-infected patients were: 83% male, mean age 54 years; 26 genotype 1a, 30 1b, 2 untypable; 64% F4; 40% were treatment-naive, 14% relapsers, 12% partial responders, 31% null responders and 3% no data. In co-infected patients: 84% male, mean age 50 years; 17 genotype 1a, 71b, 1 untypable; 92% F4; 40% were treatment-naive, 28% relapsers, 12% partial responders, 12% null responders and 8% no data. We were able to assess the effectiveness of treatment in 71 patients, who achieved 60 weeks of treatment: 51 mono-infected and 20 co-infected. In the mono-infected group: 21 (41%) achieved SVR (86% treatment-naive or relapsers), 20 (39%) had a detectable viral load (50% null responders) (3 boceprevir-treated) and 10 (20%) discontinued treatment due to toxicity or disease progression. This compared with 11 (55%) (73% treatment-naive or relapsers), 8 (40%) (38% null responders) and 1 (5%) in the co-infected group. Adverse events were: anaemia 58%, neutropenia 81% and thrombocytopenia 36% in mono-infected vs. 44%, 80% and 52% in co-infected patients. Conclusion: The rate of SVR was about 50%, higher in co-infected than in mono-infected HCV patients. However, it may have been affected by a greater proportion of null responders in the mono-infected group (p > 0.05), because as in published trials, the rates of SVR differed among patients with different responses to previous treatments. References and/or Acknowledgements: Zeuzem S, Andreone P, Pol S, et al . Telaprevir for retreatment of HCV infection. N Engl J Med 2011;364:2417–28 Jacobson IM, McHutchison JG, Dusheiko G, et al . Telaprevir for previously untreated chronic hepatitis C virus infection. N Engl J Med 2011;364:2405–16 No conflict of interest.